Conservation of livestock biodiversity and its relevance to food security - Negussie, E.; Ayalew, W. (Ethiopian Society of Animal Production, 2002)
The genetic diversity in livestock is manifested int he population numbers, varieties of sub populations and variabilities within populations of livestock. The rising demand on the earth's natural and cultivated resources to feed and sustain human life has led to a serious depletion in the diversity of plant and animal life forms in both developed and developing countries. The future of sustainable agriculture depends on the availability of a sufficiently large gene pool firm which useful genes can be selected. Since demands of the future are largely unknown agro-biodiversity also provides the reservoir of genes to respond to changes in production circumstances, market needs or disease challenges. Genetic diversity is highly relevant in Africa where specific adaptive attributes of indigenous animal genetic resources are vital, and where the production systems depend not on external inputs, but rather on the capacity of genetic resources to thrive under unfavourable environment, like the extremes of climate, disease challenge, and poor plane of nutrition. Many of the existing breeds are, however, declining in numbers due to indiscriminate crossbreeding and gradual replacement by a few exotic and supposedly more productive breeds. Moreover, it is not only these genetic resources and the production systems that they support that arse under threat but also the accompanying local knowledge, skills and culture of the communities. Biodiversity is essential to food security not only in the provision of the means to food production in time and space, but also in improving access to the food as well as its effective utilization.